Hexagonal Boron Nitride Decorated Polypropylene Separator for Dendritic Free Sodium Deposition and Stripping - Garg S.; Singh A.K.; Parmar A.S.; Rosy (My University, 2025)
Sodium metal, with its impressive electrochemical properties, including a high specific capacity of 1166 mAhg−1 and a low redox potential of −2.71 V vs SHE, emerges as a compelling option for battery anodes. However, the dendrites formed during subsequent charging/discharging cycles severely limit its practical implementation. Here, we report the ability of hexagonal boron nitride (hBN) coated polypropylene separator to suppress the dendritic deposition. The tailored separator manifests improved wettability and stable electrochemical performance under limited Na availability. The improved performance is ascribed to the sodiophilic character of hBN, which is expected to provide uniform Na+ flux and exhibit a guiding effect for uniform Na deposition. This study aims to report the use of a hBN coated separator for mitigating Na dendrites; however, comprehensive research is required to properly evaluate the pragmatic application of the proposed strategy in metal batteries. © 2023 The Electrochemical Society (“ECS”). Published on behalf of ECS by IOP Publishing Limited.